Advances in Geometric Modeling and Processing 6th International Conference, GMP 2010, Castro Urdiales, Spain, June 16-18, 2010. Proceedings - Mourrain, Bernard; Schaefer, Scott; Xu, Guoliang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Conference on Geometric Modeling and Processing, GMP 2010, held in Castro Urdiales, Spain, in June 2010. The 20 revised full papers presented were carefully reviewed and selected from a total of 30 submissions. The papers cover a wide spectrum in the area of geometric modeling and processing and address topics such as solutions of transcendental equations; volume parameterization; smooth curves and surfaces; isogeometric analysis; implicit surfaces; and computational geometry.
Global Solutions of Well-Constrained Transcendental Systems Using Expression Trees and a Single Solution Test -- Surfaces with Rational Chord Length Parameterization -- Support Function of Pythagorean Hodograph Cubics and G 1 Hermite Interpolation -- Piecewise Tri-linear Contouring for Multi-material Volumes -- An Efficient Algorithm for the Sign Condition Problem in the Semi-algebraic Context -- Constraints on Curve Networks Suitable for G 2 Interpolation -- Computing the Distance between Canal Surfaces -- A Subdivision Approach to Planar Semi-algebraic Sets -- Non-manifold Medial Surface Reconstruction from Volumetric Data -- Decomposing Scanned Assembly Meshes Based on Periodicity Recognition and Its Application to Kinematic Simulation Modeling -- Automatic Generation of Riemann Surface Meshes -- G 1 Bézier Surface Generation from Given Boundary Curve Network with T-Junction -- Efficient Point Projection to Freeform Curves and Surfaces -- Construction of Minimal Catmull-Clark s Subdivision Surfaces with Given Boundaries -- Parameterization of Star-Shaped Volumes Using Green s Functions -- Optimal Analysis-Aware Parameterization of Computational Domain in Isogeometric Analysis -- Construction of Subdivision Surfaces by Fourth-Order Geometric Flows with G 1 Boundary Conditions -- Efficient Computation of 3D Clipped Voronoi Diagram -- Selecting Knots Locally for Curve Interpolation with Quadratic Precision -- Eigenmodes of Surface Energies for Shape Analysis.
Keywords: Computer science; Computer software; Computational complexity; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Computer Graphics; Discrete Mathematics in Computer Science; Algorithm Analysis and Problem Complexity; Pattern Recognition; Image Processing and Computer Vision; Computer Imaging, Vision, Pattern Recognition and Graphics